INVESTIGATING THE USE AND SEMANTIC INTERPRETATION OF FIGURATIVE LANGUAGE IN EFL STUDENTS’ LITERARY WORK - Sudar, Sudar (English Review: Journal of English Education, 2024)
This study aims to investigate the types of figurative language written in the students’ literary work, to identify the dominant of figurative language written in the students’ literary work, and to interpret the meaning of figurative language written in the student’s literary work. This is descriptive qualitative research. The scenario of taking the data were as follow; first, researcher took the data from the literary classroom. Second, researcher identify figurative language taken from student’s literary work. Third, interpreting the data based on the theory of figurative language written by Fatimah, Amri, and Rusan, (2020) and the theory of meaning developed by Umagandhi and Vinothini, (2017). Research findings stated there were six types of figurative language written by students in their literary works. Then, the dominant of figurative language written by students was hyperbole figurative and personification. Further, there were four types of semantics meaning written by students, such as; connotative, affective, reflected, and associative. Affective semantic meaning was the dominant meaning written in the students’ literary work. Affective meaning was found in the Personification figurative language. Further, Figurative languages and their semantics meaning were meaningful for learning and empowering students’ linguistics’ competences. Particularly it is in semantics discussion.